2014
DOI: 10.4238/2014.september.29.5
|View full text |Cite
|
Sign up to set email alerts
|

Screening for key genes associated with invasive ductal carcinoma of the breast via microarray data analysis

Abstract: ABSTRACT. The aim of this study was to identify key genes related to invasive ductal carcinoma (IDC) of the breast by analyzing gene expression data with bioinformatic tools. Microarray data set GSE31138 was downloaded from Gene Expression Omnibus, including 3 breast cancer tissue samples and 3 normal controls. Differentially expressed genes (DEGs) between breast cancer and normal control were screened out (FDR < 0.05 and |logFC| > 2). Coexpression between genes was examined with String, and a network was then… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…As presented in Figure 1C, these DEGs were significantly enriched in 19 signaling pathways: the ECM-receptor interaction signaling pathway (p<0.001), malaria (p=0.013), staphylococcus aureus infection (p=0.002), lysosome (p=0.003), ABC transporters (p=0.003), focal adhesion (p=0.005), the PPAR signaling pathway (p=0.01), axon guidance (p=0.011), regulation of lipolysis in adipocytes (p=0.012), protein digestion and absorption (p=0.016), phagosome (p=0.019), hematopoietic cell lineage (p=0.036), biosynthesis of amino acids (p=0.047), the PI3K-Akt signaling pathway (p=0.058), proteoglycans in cancer (p=0.064), the Rap1 signaling pathway (p=0.088), the adipocytokine signaling pathway (p=0.092), biosynthesis of antibiotics (p=0.093), and the AMPK signaling pathway (p=0.095). Among them, the ECM-receptor interaction signaling pathway plays a crucial role in modulating breast cancer metastasis (14)(15)(16). Therefore, DEGs in the ECMreceptor interaction signaling pathway were prioritized for further examination in this study.…”
Section: Analysis Of Putative Biological Function Of Degs Through Pathway Enrichment Analysismentioning
confidence: 99%
“…As presented in Figure 1C, these DEGs were significantly enriched in 19 signaling pathways: the ECM-receptor interaction signaling pathway (p<0.001), malaria (p=0.013), staphylococcus aureus infection (p=0.002), lysosome (p=0.003), ABC transporters (p=0.003), focal adhesion (p=0.005), the PPAR signaling pathway (p=0.01), axon guidance (p=0.011), regulation of lipolysis in adipocytes (p=0.012), protein digestion and absorption (p=0.016), phagosome (p=0.019), hematopoietic cell lineage (p=0.036), biosynthesis of amino acids (p=0.047), the PI3K-Akt signaling pathway (p=0.058), proteoglycans in cancer (p=0.064), the Rap1 signaling pathway (p=0.088), the adipocytokine signaling pathway (p=0.092), biosynthesis of antibiotics (p=0.093), and the AMPK signaling pathway (p=0.095). Among them, the ECM-receptor interaction signaling pathway plays a crucial role in modulating breast cancer metastasis (14)(15)(16). Therefore, DEGs in the ECMreceptor interaction signaling pathway were prioritized for further examination in this study.…”
Section: Analysis Of Putative Biological Function Of Degs Through Pathway Enrichment Analysismentioning
confidence: 99%
“…A recent study performed in the breast cancer cell line MCF-7 revealed that the reduction of COL4A2 mRNA levels by miR-29b may contribute to the invasiveness of MCF-7 cells [25]. It has been postulated that extracellular matrix-related COL4A2 is associated with breast cancer and may be a potential biomarker for early diagnosis and therapy of breast cancer [26]. All of the aforementioned studies suggest that COL4A2 may play a role in the pathogenesis of cancer, notably breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating evidences demonstrated that CETN2 was identified in various types of cancers. Huan et al revealed that CETN2 was associated with invasive ductal carcinoma of the breast, and might be potential biomarker for breast cancer [ 29 ]. It was reported that the down-regulated of CETN2 might have tumor suppressive function in bladder cancer [ 30 ].…”
Section: Discussionmentioning
confidence: 99%